A Decade of Boon or Burden: What Has the CHIP Ever Done for Cellular Protein Quality Control Mechanism Implicated in Neurodegeneration and Aging? - Joshi, Vibhuti; Amanullah, Ayeman; Upadhyay, Arun; Mishra, Ribhav; Kumar, Amit; Mishra, Amit (Frontiers in Molecular Neuroscience, 2016)
Cells regularly synthesize new proteins to replace old and abnormal proteins for normal cellular functions. Two significant protein quality control pathways inside the cellular milieu are ubiquitin proteasome system (UPS) and autophagy. Autophagy is known for bulk clearance of cytoplasmic aggregated proteins, whereas the specificity of protein degradation by UPS comes from E3 ubiquitin ligases. Few E3 ubiquitin ligases, like C-terminus of Hsc70-interacting protein (CHIP) not only take part in protein quality control pathways, but also plays a key regulatory role in other cellular processes like signaling, development, DNA damage repair, immunity, and ageing. CHIP targets misfolded proteins for their degradation through proteasome, as well as autophagy; simultaneously, with help of chaperones, it also regulates folding attempts for misfolded proteins. The broad range of CHIP substrates and their association with multiple pathologies makes it a key molecule to work upon and focus for future therapeutic intervention. E3 ubiquitin ligase CHIP interacts and degrades many protein inclusions formed in neurodegenerative diseases. The presence of CHIP at various nodes of cellular protein-protein interaction network presents this molecule as a potential candidate for further research. In this review, we have explored a wide range of functionality of CHIP inside the cell by a detailed presentation of its co-chaperone, E3 and E4 enzyme like functions, with central focus on its protein quality control roles in neurodegenerative diseases. We have also raised many unexplored but expected fundamental questions regarding CHIP functions, which generate hopes for its future applications in research, as well as drug discovery.